2018
DOI: 10.3892/mmr.2018.8413
|View full text |Cite
|
Sign up to set email alerts
|

The human umbilical cord stem cells improve the viability of OA degenerated chondrocytes

Abstract: Osteoarthritis (OA) affects a large number of patients; however, human umbilical cord stem cells exhibit therapeutic potential for treating OA. The aim of the present study was to explore the interaction between human umbilical cord stem cells and degenerated chondrocytes, and the therapeutic potential of human umbilical cord stem cells on degenerated chondrocytes. Human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) were harvested from human umbilical cords, and flow cytometry was used to analyze th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 47 publications
(46 reference statements)
2
26
0
1
Order By: Relevance
“…Another alternative for OA treatment with MSCs are human umbilical cord-derived MSCs (hUC-MSCs). These cells enhance the proliferation of OA chondrocytes and downregulate the expression of inflammatory cytokines, moreover, the co-culture of hUC-MSCs and OA chondrocytes may to be a therapeutic option for OA [ 22 ]. hUC-MSCs could be an alternative to BMMSCs for clinical applications, due to their easy preparation and low risk of viral contamination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another alternative for OA treatment with MSCs are human umbilical cord-derived MSCs (hUC-MSCs). These cells enhance the proliferation of OA chondrocytes and downregulate the expression of inflammatory cytokines, moreover, the co-culture of hUC-MSCs and OA chondrocytes may to be a therapeutic option for OA [ 22 ]. hUC-MSCs could be an alternative to BMMSCs for clinical applications, due to their easy preparation and low risk of viral contamination.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in Shangai suggested that the secretion of hUC-MSCs enhanced chondrocyte proliferation and showed that these stem cells increased expression of chondrogenic genes ( aggrecan, sox-9, collagen II ), indicating chondrocytes promoted chondrogenic differentiation of hUC-MSCs, compared to the control group. They also postulated that hUC-MSCs inhibited inflammatory activity in OA chondrocytes [ 22 ]. In the same line, Zheng et al (2013) reported the chondrogenic differentiation of hUC-MSCs by co-culture with rabbit chondrocytes [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two articles reported the use of coculture systems combining HWJSC with human articular chondrocytes or osteoarthritis cells to allow these latter cell types to induce HWJSC differentiation. 41,42 The results suggested that coculture was able to promote chondrogenesis, and certain genes, including COL1A1, COMP, TGFb1, ACAN, and SOX9, were upregulated in differentiated HWJSC.…”
Section: Mesodermal Differentiation Potential Of Hwjscmentioning
confidence: 98%
“…Preliminary in vitro results on cocultures between wjMSCs and ILβ1-stimulated chondrocytes showed reduced expressions of cartilage-degrading enzymes, such as MMP-1 and MMP-3, as compared to ILβ1-stimulated chondrocytes alone [40]. The same decrease was observed also in OA chondrocytes after cocultures with wjMSCs [41]. Taken together, these results suggest a protective effect of wjMSCs on damaged chondrocytes and have been confirmed in vivo, whereby the injection of wjMSCs in rat models of OA showed reduced secretions of cartilage-degrading enzymes [42], inflammatory cytokines [43], increased cartilage matrix production and decreased chondrocyte apoptosis [44].…”
Section: Cord Blood and Wharton's Jelly Mscs For Oa And Ra Therapymentioning
confidence: 76%